Outcome of Epidermal Growth Factor Receptor Mutated and Non Mutated Adenocarcinoma Lung to Standard Therapy - Dulal, Soniya; Mishra, Akshat; Shah, Aarati; Acharya, Bibek; Shilpakar, Ramila; Chapagain Acharya, Sandhya; Karn, Ambuj; Sharma, Rajeev; Gautam, Balram; Paudel, Bishnu Dutta (Journal of Nepal Health Research Council, 2023)
Background: Asian patients with adenocarcinoma of lung have higher incidence of epidermal growth factor receptor mutations which predict increased response and survival in patients to oral tyrosine kinase inhibitors. This study was conducted to study the frequency of epidermal growth factor receptor mutation in patients in Nepal and compare the outcome in epidermal growth factor receptor mutated versus non-mutated patients receiving standard therapy.Methods: This is an observational study conducted among newly diagnosed patients with stage IV adenocarcinoma of lung in Bir Hospital from April 2017 to June 2018. Demographic and clinical data collection along with epidermal growth factor receptor mutation testing was done. Patients with epidermal growth factor receptor mutations received Gefitinib while non-mutated patients received systemic chemotherapy. Response evaluation, progression free survival at 1 year, objective response rate and quality of life were compared. Follow up period was for 1 year.Results: Eighty three (33%, n=253) patients were diagnosed with adenocarcinoma of the lung with mean age at diagnosis being 59.4 years. epidermal growth factor receptor mutations were found in 29% patients. Complete response was achieved in 9.1% vs 3.0 % (p=0.46), objective response rate was 27.3% versus 15.2% (p=0.23), progression free survival at 1 year was 39% vs 27%, (p = 0.29) and mean score of global health status was 68.1 versus 61.6 in epidermal growth factor receptor mutated versus non-mutated (p = 0.036). Conclusions: The frequency of epidermal growth factor receptor mutation in patients with adenocarcinoma of the lung was lower than in Eastern Asian studies, but higher than in western populations. epidermal growth factor receptor mutated patients had improved survival, better treatment response and quality of life in comparison with non-mutated. Keywords: Adenocarcinoma of lung; EGFR; quality of life